Expression of Disialoganglioside (GD2) in Neuroblastic Tumors: A Prognostic Value for Patients Treated With Anti-GD2 Immunotherapy. (July 2018) - Terzic, Tatjana; Cordeau, Martine; Herblot, Sabine; Teira, Pierre; Cournoyer, Sonia; Beaunoyer, Mona; Peuchmaur, Michel; Duval, Michel; Sartelet, Herve
Neuroblastoma, a malignant neoplasm of the sympathetic nervous system, is one of the most aggressive pediatric cancers. Patients with stage IV high-risk neuroblastoma receive an intensive multimodal therapy ending with an immunotherapy based on a chimeric monoclonal antibody ch14.18. Although the use of ch14.18 monoclonal antibody has significantly increased the survival rate of high-risk neuroblastoma patients, about 33% of these patients still relapse and die from their disease. Ch14.18 targets the disialoganglioside, GD2, expressed on neuroblastic tumor (NT) cells. To better understand the causes of tumor relapse following ch14.18 immunotherapy, we have analyzed the expression of GD2 in 152 tumor samples from patients with NTs using immunohistochemical stainings. We observed GD2 expression in 146 of 152 samples (96%); however, the proportion of GD2-positive cells varied among samples. Interestingly, low percentage of GD2-positive cells before immunotherapy was associated with relapse in patients receiving ch14.18 immunotherapy. In addition, we demonstrated in vitro that the sensitivity of neuroblastoma cell lines to natural killer-mediated lysis was dependent on the proportion of GD2-positive cells, in the presence of ch14.18 antibody. In conclusion, our results indicate that the proportion of tumor cells expressing GD2 in NTs should be taken in consideration, as a prognostic marker, for high-risk neuroblastoma patients receiving anti-GD2 immunotherapy.